Perlindungan Hukum Terkait Kepemilikan Tanah Oleh Pihak Ketiga Berdasarkan Putusan Peninjuan Kembali - Maxie Sinay; Merry Tjoanda; Ronald Saija (Faculty of Law, Universitas Pattimura, 2022)
Introduction: Legal protection related to land ownership by third parties based on the request civil Number 339 PK / Pdt / 2013.Purposes of the Research: Reviewing and discussing forms of legal protection for land ownership by third parties. Methods of the Research: This research uses the juridical normative method by using a statutory approach, a conceptual approach, and a case approach.Results of the Research: The results of the study show that based on the Judicial Review Decision No. 339/PDT/2013. Lenny as the plaintiff is the legal owner based on the transfer of Ownership rights to the land according to Article 20 of Law No. 5 of 1960 concerning Basic Agrarian Regulations Jo. Article 37 PP No. 24 of 1997 concerning Land Registration and the land sale and purchase agreement made by Lenny was in accordance with the terms of the agreement as referred to in Article 1320 of the Civil Code. Lenny also has an Object of dispute in good faith. The object of the dispute must be executed immediately and against a civil lawsuit by the opposing party, namely Tan Pallar as long as the lawsuit is about the same object of the lawsuit and the subject of the same lawsuit in the same relationship, then the lawsuit must be rejected because there has been a previous decision, namely the Judicial Review Decision No. 339 PK/PDT/2013 which already has permanent legal force.